FENOMENA SEKS DALAM NOVEL INDONESIA MUTAKHIR KARYA PENGARANG PEREMPUAN: KAJIAN KRITIK SASTRA FEMINIS - . Wiyatmi (Humaniora, 2006)
This research is aimed at describing and understanding (1) homosexuality phenomena in the current Indonesian novels, (2) the relationship between homosexuality phenomena with the existence of homosexual community in Indonesia, and(3) the relationship between homosexuality phenomena with feminist school. To achieve these aims, six novels are analyzed. They are (1) Larung by Ayu Utami, (2) Supernova by Dee (Dewi) Lestari, (3) Mahadewi Mahadewi (4) Garis Tepi Seorang Lesbian by Herlinatien, (5) Tabularasa by Ratih Kumala, and (6) Dadaisme by Dewi Sartika. The result of the research shows that (1) homosexuality phenomena in the current Indonesian novels are reflected in theme and character problems, (2) these phenomena are related to the existence of homosexual community in Indonesia, whose members already demand that their existence be recognized in society, and (3) these phenomena are related to feminism, especially radical feminism that influences the authors’ creativity.